Remote assessment of hand dexterity: an quantitative method to reduce human error in occupational therapy. Issue 1 (31st December 2022) - Acharya K, Aneesha; Bhat, Somashekara; M, Kanthi; Cheema, Sarthak; Kolekar, Sucheta V.
Abstract: Dexterity is the coordination of hands and fingers with the eyes. Existing unilateral movements and dexterity tests use wearable devices for recording hand assessment. It is understandable that whenever some wired devices tag hands, the patient tends to be more conscious, which may not reflect the actual outcome. In this paper, using the finger-tap counter and loop-wire test, an attempt is made to evaluate unilateral movements and dexterity in adults of different age groups without using any wearable device. The test timings are recorded automatically with the help of the ATmega328p microcontroller and transferred to the clinician wirelessly via Bluetooth communication. Healthy 30 subjects between the age range (20–35, 36–50, 51–65, 66–80) were tested for finger-tap counter and loop-wire tests. The experiment is also tested for dominant and non-dominant hands for the same subjects. In this experiment, the result shows as the age increases, the trend in the assessment completion time and number of failures during the performance of the test increases. Female groups can perform both tests quicker than male groups with fewer errors irrespective of age group.